The Use of Herbal Medicine and Medicinal Plants as Immunity Enhancers for Migrant Workers in Malaysia by Utilizing Herbal Plants Around the House as Body Immune Enhancers - ahwan, ahwan (Universitas Sahid Surakarta, 2025)
Indonesian migrant workers in Malaysia face various challenges, including limited access to health services and vulnerability to diseases due to demanding working conditions and unfamiliar environments. This community service aims to increase knowledge and skills regarding the use of traditional medicinal plants to improve immunity. The method used is to provide training materials on identifying, processing, and consuming available medicinal plants safely. Evaluation of this community service activity showed an increase in participants' knowledge about traditional medicine, its benefits, and safe use practices. The long-term goal is to encourage sustainable practices in utilizing local herbal resources for self-care among PMI in Malaysia, which contributes to their overall health, productivity, and well-being while preserving traditional Indonesian medicinal practices.